Science, Technology, and Innovation : Capacity Building for Sustainable Growth and Poverty Reduction - Watkins, Alfred; Ehst, Michael (Washington, DC : World Bank, 2012)
The cases from the forum presented here capture the lessons from the science, technology, and innovation (STI) capacity building experiences of both developing and industrial countries (governments working in partnership with the private sector, nongovernmental organizations, academia, and development partners). These cases highlight ways that STI capacity building programs have enabled countries to achieve the following: (i) provide essential services, such as access to clean drinking water in rural villages and availability of affordable, reliable energy sources; (ii) exploit opportunities to produce higher-productivity, value-added agriculture crops; (iii) transition from exporting unprocessed raw materials to exporting value-added products and from low-skilled assembly operations to higher-skilled manufacturing processes; (iv) create benefits from an increasingly open trading system and increased flows of foreign direct investment (FDI) by proactively generating spillovers to the local economy; and (v) maintain competitiveness in a rapidly changing global economy marked by rapid technological change. History suggests that these challenges are daunting, but they are not impossible to overcome. Many countries have managed to build the STI capacity they needed to thrive and prosper. So that other countries may profit from lessons learned, the global forum discussed what these countries achieved and how they achieved what they did. The collective task is to help countries convert these lessons of experience into specific STI capacity building programs that can be implemented on the ground and that will have a significant, measurable impact on people's lives.